Composition and Distribution of Income Among the Sheep Heahing Nomads - Chauhan, S K (Annals of Arid Zone, 2016)
Farmers of the tribal area of Chamba district in Himachal Pradesh are mainly dependent on sheep rearing for their livelihood which significantly contribute towards the total household income. The variability in agricultural income was quite high on small farms compared to medium and large farms. However, the income variability registered reduction with the introduction of sheep rearing. Relatively more uniform distribution of income was observed in case of large farms.